Орнамент тканих литовських народних поясів у кроскультурній перспективі: аналоги в енеолітичних культурах Давньої Європи - Туменас, В. (Народна творчість та етнологія, 2011)
The author analyzes the main motifs of the Lithuanian woven belts, ascertains their primordial historical roots. Also he traces their typological connection with the oldest similar geometrical ornament existed in the territory of Eastern Europe – in the culture Trypillia-Cucuteni (Ukraine, Romania) of eneolithic Old Europe civilization.